On the Homonymy of Paralinguistic Means - Barotova, Muxiba Orifovna (The Lingua Spectrum, 2026)
This article provides a theoretical and scientific analysis of the phenomenon of homonymy in paralinguistic means. It highlights the role of paralinguistic units in the communicative process, as well as their semantic and pragmatic features. Furthermore, the homonymous nature of nonverbal units that share the same form but express different meanings is revealed through illustrative examples. The results of the study are of significant importance for the fields of paralinguistics and speech culture. The article emphasizes that studies on paralinguistic means have increasingly become a subject of growing interest in both world and Uzbek linguistics. In particular, it highlights the insufficient investigation of semantic relations among paralinguisms, as well as the interrelations between verbal and nonverbal units. The present article mainly focuses on the homonymous features of kinetic paralinguistic means. Based on textual examples drawn from Uzbek prose literature, it reveals cases of formal similarity among paralinguisms formed through movements of the head and hands. In Uzbek linguistics, the scientific foundation of nonverbal communication studies has not yet been fully established. Investigating the issue of homonymy contributes to revealing the semantic potential of the paralinguistic system. Uzbek gestures and mimetic expressions are closely connected with the national mentality; therefore, their polysemy reflects the communicative culture of the people.